MVA-HBVac—A novel vaccine vector that allows pan-genotypic targeting of hepatitis B virus by therapeutic vaccination - Kosinska, Anna D.; Kächele, Martin; Kerth, Helene A.; Mück-Häusl, Martin; Ates Öz, Edanur; Gültan, Merve; Hansen-Palmus, Lea; Sacherl, Julia; Ko, Chunkyu; Festag, Julia; Lehmann, Michael H.; Mogler, Carolin; et al. (Molecular therapy. Nucleic acids, 2025)
Therapeutic vaccination holds the promise to cure chronic hepatitis B virus (HBV) infection. We hypothesize that B cell, CD4, and CD8 T cell responses are necessary to overcome HBV-specific immune tolerance in chronic infection because they accompany the rare, spontaneous resolution of chronic HBV infection. Therefore, we designed the heterologous prime-boost vaccine TherVacB in which virus-like particle vaccination stimulates B and helper CD4 T cells and primes cytotoxic effector CD8 T cells and a vector boost expands the T cell response. Here, we report the generation and characterization of a novel modified vaccinia virus Ankara (MVA)-based vector, MVA-HBVac, capable of inducing strong and multi-specific T cell responses against the immunodominant epitopes of four different viral proteins covering >95% of HBV strains circulating worldwide. When MVA-HBVac was administered after a prime with adjuvanted hepatitis B S- and core-antigens forming virus-like particles, it activated strong HBV-specific CD4 and CD8 T cell responses against the major HBV antigens in vivo in naive and HBV carrier mice. This induced a sustained antiviral effect against different, clinically relevant HBV genotypes. Our data showed that the TherVacB regimen employing the novel, pan-genotypic MVA-HBVac vector could overcome HBV-specific immune tolerance and lead to the initiation of clinical trials evaluating the therapeutic vaccine. [Display omitted] Ulrike Protzer and colleagues developed a novel therapeutic hepatitis B vaccine vector, MVA-HBVac, designed to target 95% of circulating HBV isolates worldwide. Administration of MVA-HBVac following two protein prime immunizations in the TherVacB vaccination scheme induced strong HBV-specific T cell responses and reduced or even “cured” HBV in mice carrying various HBV genotypes.